Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Intensitas Nyeri Pasien Pasca Operasi Seksio Sesarea Hari Pertama - Ni Wayan Noviani, Fitria, Ni Made Darmiyanti, (STIKes Budi Mulia Sriwijaya, 2026)
This study aimed to evaluate the effectiveness of Progressive Muscle Relaxation (PMR) on pain intensity in post-cesarean section patients on the first postoperative day. Method A quasi-experimental design with a non-randomized control design was conducted at the General Hospital of Negara Regency, Bali Province, from March to May 2025. A total of 60 post-cesarean section patients were recruited using purposive sampling and allocated into two groups: the intervention group (n=30) received a single 20-minute session of PMR, while the control group (n=30) received standard care. Pain intensity was measured using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using paired and independent t-tests. The intervention group demonstrated a significant reduction in pain intensity, with mean VAS scores decreasing from 6.8 ± 1.1 to 3.9 ± 1.0 (mean difference = 2.9; p<0.001; Cohen’s d = 2.6). In contrast, the control group showed no significant change (6.7 ± 1.2 to 6.1 ± 1.0; mean difference = 0.6; p=0.064). The between-group difference was statistically significant (p<0.001). PMR is effective in reducing pain intensity in post-cesarean section patients on the first postoperative day. This non-pharmacological technique can be integrated into standard postpartum care as a safe, low-cost intervention to enhance maternal comfort and reduce reliance on analgesics